Lidocaine and Bupivacaine Downregulate MYB and DANCR lncRNA by Upregulating miR-187-5p in MCF-7 Cells - Lin, Chiao-Yi; Tseng, Wen-Ting; Chang, Yao-Yin; Tsai, Mong-Hsun; Chuang, Eric Y.; Lu, Tzu-Pin; Lai, Liang-Chuan (Frontiers in Medicine, 2022)
Background: Breast cancer is the most common malignancy and a leading cause of death among women. The majority of patients require surgery, and retrospective studies have revealed an association between anaesthetic techniques during surgery and clinical outcomes. Local anaesthetics (LAs) influence carcinogenesis by interacting with non-coding RNAs (ncRNAs). However, the detailed mechanisms underlying the association between LAs and ncRNAs remain unclear. Methods: In this study, the effects of two commonly used LAs, lidocaine and bupivacaine, on the malignancy of MCF-7 breast cancer cells were investigated. The expression profiles of the microRNAs (miRNAs) that responded to treatment with LAs were determined through next-generation sequencing. Results: Data from the functional assay revealed that the LAs suppressed the proliferation of MCF-7 cells. The result of next-generation sequencing revealed that 131 miRNAs were upregulated, following treatment with the LAs. Validation using polymerase chain reaction (PCR) identified miR-187-5p as a potential biomarker, and it was selected for further analyses. Prediction with bioinformatics tools and luciferase reporter assays revealed that MYB is a direct target gene of miR-187-5p. Based on the hypothesis that lncRNAs acts as miRNA sponges, the target lncRNA, DANCR, of miR-187-5p was predicted using DIANA-LncBase v2 and validated using luciferase reporter assays. In addition, the reciprocal suppressive effect between DANCR and miR-187-5p was determined. Conclusions: This study demonstrated that the anti-tumour properties of lidocaine and bupivacaine were mediated through the DANCR-miR-187-5p-MYB axis. This provides a novel molecular mechanism of tumour suppression in breast cancer.